2017
DOI: 10.1111/jnc.14128
|View full text |Cite
|
Sign up to set email alerts
|

Deleting the Arntl clock gene in the granular layer of the mouse cerebellum: impact on the molecular circadian clockwork

Abstract: The suprachiasmatic nucleus houses the central circadian clock and is characterized by the timely regulated expression of clock genes. However, neurons of the cerebellar cortex also contain a circadian oscillator with circadian expression of clock genes being controlled by the suprachiasmatic nucleus. It has been suggested that the cerebellar circadian oscillator is involved in food anticipation, but direct molecular evidence of the role of the circadian oscillator of the cerebellar cortex is currently unavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(67 reference statements)
0
11
0
Order By: Relevance
“…In primates, however, PER1/2‐ir is expressed in the Purkinje cell layer (the primary output of the cerebellum), but not the granule or molecular cell layers, with higher expression during the day (ZT 10) compared to the night (ZT 19; Guissoni Campos et al., ). Bmal1 deletion specifically in granule cells renders expression of the majority of clock genes arrhythmic; however, circadian locomotor behavior is not significantly changed (Bering, Carstensen, & Rath, ). Although the cerebellum has >2,000 rhythmic transcripts (detected in animals housed in DD for two cycles; (Pizarro, Hayer, Lahens, & Hogenesch, ), it is surprising that we know very little about the function of the molecular clock in this important area of the brain.…”
Section: Metencephalon (Hindbrain): Cerebellummentioning
confidence: 99%
“…In primates, however, PER1/2‐ir is expressed in the Purkinje cell layer (the primary output of the cerebellum), but not the granule or molecular cell layers, with higher expression during the day (ZT 10) compared to the night (ZT 19; Guissoni Campos et al., ). Bmal1 deletion specifically in granule cells renders expression of the majority of clock genes arrhythmic; however, circadian locomotor behavior is not significantly changed (Bering, Carstensen, & Rath, ). Although the cerebellum has >2,000 rhythmic transcripts (detected in animals housed in DD for two cycles; (Pizarro, Hayer, Lahens, & Hogenesch, ), it is surprising that we know very little about the function of the molecular clock in this important area of the brain.…”
Section: Metencephalon (Hindbrain): Cerebellummentioning
confidence: 99%
“…The first study of FAA in Bmal1 −/− mice showed that these mice had no FAA but that FAA was rescued by injecting virus expressing Bmal1 into the dorsomedial nucleus of the hypothalamus (Fuller et al, 2008). However, several independent laboratories have since demonstrated that Bmal1 −/− mice had FAA (Mistlberger et al, 2008; Pendergast et al, 2009; Storch and Weitz, 2009; Mieda and Sakurai, 2011; Takasu et al, 2012; Izumo et al, 2014, Bering et al, 2017). The discrepancy in results could be attributed, in part, to the fact that Bmal1 −/− mice may have been ill during restricted feeding in the Fuller et al study because food availability was not gradually reduced (for further discussion of FAA in Bmal1 −/− mice, see Fuller et al, 2009; Mistlberger et al, 2009b; Mistlberger et al, 2009a).…”
Section: Circadian Gene Mutant Mice and Faamentioning
confidence: 99%
“…The discrepancy in results could be attributed, in part, to the fact that Bmal1 −/− mice may have been ill during restricted feeding in the Fuller et al study because food availability was not gradually reduced (for further discussion of FAA in Bmal1 −/− mice, see Fuller et al, 2009; Mistlberger et al, 2009b; Mistlberger et al, 2009a). Mice lacking functional BMAL1 in the nervous system, forebrain, or cerebellar granule cells also had intact FAA (Mieda and Sakurai, 2011; Izumo et al, 2014; Bering et al, 2017). In sum, numerous studies performed in different laboratories have demonstrated that BMAL1 is not necessary for FAA.…”
Section: Circadian Gene Mutant Mice and Faamentioning
confidence: 99%
“…However, circadian oscillators characterized by circadian rhythms in clock gene expression are also present in extra-hypothalamic structures, including both peripheral tissues and various parts of the central nervous system [3,4]. All known clock genes are expressed in the granular and Purkinje cell layers of the cerebellar cortex [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%